Узгодженість між стандартними методами діагностики харчової гіперчутливості у дітей різного віку - Пахольчук, Олексій Петрович; Недельська, Світлана Миколаївна; Pakholchuk, O. P.; Nedelska, S. M. (My University, 2018)
The objective was to study agreement between standard methods of food hypersensitivity diagnostics. Materials and methods. 424 patients aged 26,3 (12,1; 54,25) months were included in the study. Methods included skin prick-test, specific IgE (sIgE) detection, oral provocation test (OPT). Results. Statistically significant difference was identified between age periods by results of the analysis of the anamnesis (Kruskal–Wallistest: H (4, N = 424) = 16,4; p = 0,003), OPT H (4, N = 196) = 29,5; p = 0,001) and its’ combination (H (4, N = 196) = 29,50; p = 0,001). Agreement between tests in patients aged up to 1 y.o. was unsatisfying. In children older than 1 y.o. moderate agreement was identified between sIgE detection and prick-test (κ = 0,5 (95% CІ = 0,4–0,59), sIgE and OPT (κ = 0,5 (95% CІ = 0,47–0,53). Conclusions. Standard tests of the diagnostics of the skin food hypersensitivity symptoms, especially in children up to 1 y.o., can not be used interchangeably.
Agreement between standard methods of Food hypersensitivity diagnostics in children
Keywords: харчова гіперчутливість; діти; прик-тест; оральна провокаційна проба; каппа Коена; узгодженість; food hypersensitivity; children; prick-test; oral provocation test; Cohen’s kappa; agreement